Intuitionistic Fuzzy Sets: Theory and Applications - MAKHLOUF et TOUINA, Djamila et Wahiba (Faculty of Mathematics and Computer Sciences Department of Mathematics - Option : Algebra and Discrete Mathematics, 2020)
In this memory, ﬁrstly we reminded some concepts in the classical case, and in other we gave the concept of the fuzzy sets and their properties. Secondly, we have presented the characteristics and essential properties of the concept of intuitionistic fuzzy sets that are an extension of the concept of fuzzy sets. In more, we presented the intuitionistic fuzzy relations, the intuitionistic fuzzy lattices, the intuitionistic fuzzy ideals and intuitionistic fuzzy ﬁlters. Finally, we have studied an application of the intuitionistic fuzzy sets, where we studied the representation theory of L ukasiewicz-Moisil algebra by the notion of intuitionistic fuzzy sets.
Keywords: Fuzzy set, intuitionistic fuzzy set, intuitionistic fuzzy relations, intuitionistic fuzzy ideal, intuitionistic fuzzy ﬁlter, intuitionistic fuzzy lattice.